Private London : Private #4 - Patterson, James, 1947-; Pearson, Mark, 1960- (New York : Grand Central Pub., 2012)
Dan Carter, head of the London division of Private, the world's most exclusive detective agency, must join forces with his ex-wife if he is going to save American student Hannah Shapiro from a threat that has stalked her for eight years.
Originally published: London : Century, 2011.
Keywords: Private security services -- Fiction; Private investigators -- England -- London -- Fiction; Detectives -- London (England) -- Fiction; Suspense fiction; Mystery fiction